The experimental study of heat dissipation during fatigue crack propagation under biaxial loading - Aleksei Vshivkov; Oleg Plekhov; Anastasiia Iziumova; Aleksandr Zakharov; Valery Shlyannikov (Fracture and Structural Integrity)
The work is devoted to experimental study of heat flow evolution at the fatigue crack tip during biaxial loading. The plane samples of titanium alloy Graid-2 with thick of 1 mm were weakened by notch to initiate fatigue crack at the center of samples. Infrared thermography and the contact heat flux sensor based on the Seebeck effect are used to monitor the dissipated thermal energy. During tests the samples were subjected to cyclic loading of 10 Hz with constant stress amplitude and different biaxial coefficient.  The experimental results confirm the previous conclusions of authors about two regime of energy dissipation at fatigue crack tip. The heat dissipation curve can be divided in two stages. Under the first stage the power of heat flux is proportional to the multiplication of the crack rate by its length. In the second stage is characterized by classical linear relationship between crack rate and heat flux rom the crack tip. The qualitative correspondence of the energy approach to the classical representation based on the stress intensity factor was shown.